Cell binding, internalization and cytotoxic activity of human granzyme B expressed in the yeast Pichia pastoris - Giesübel, Ulrike (Portland Press Ltd., 2006)
Granzyme B (GrB) is an apoptosis-inducing protease of cytotoxic lymphocytes. We have investigated intracellular and extracellular effects of human GrB using recombinant protein expressed in the yeast Pichia pastoris. GrB was rapidly taken up by HeLa cells, and accumulated in vesicular structures in the cytoplasm. There it remained inactive and could not be liberated by the endosomolytic reagent chloroquine, indicating that the vesicular structures are distinct from late endosomes and lysosomes. Direct cytosolic delivery of GrB with a cationic lipid-based transduction reagent, however, resulted in the induction of apoptotic cell death. After prolonged incubation at or above 125 nM, GrB on its own induced pronounced morphological changes in human tumour cells, leading to partial loss of contact to the culture support. This extracellular effect was dependent on enzymatic activity and could be reversed by removal of the protein, suggesting GrB-dependent cleavage of extracellular matrix components as the underlying mechanism.